Electrochemical promotion of carbon supported Pt, Rh and Pd catalysts for H2 oxidation in aqueous alkaline media. Issue 6 (2nd March 2018) - Athanasiou, Michail; Hasa, Bjorn; Vakros, John; Sygellou, Labrini; Katsaounis, Alexandros
Abstract: BACKGROUND: The effect of electrochemical promotion of catalysis (EPOC) for the case of H2 oxidation reaction over commercial M (M=Pt, Rh, Pd)/Vulcan XC72 (ETEK) electrodes immersed in alkaline media was explored in this study. Various reactant mixtures (H2 and O2 ) fed simultaneously through a glass frit to the anodic electrode which was immersed in the electrolyte. Both positive and negative currents were applied between anode and cathode while all the reactants were followed by mass spectrometry. RESULTS: In the case of Pt electrode, it was found that application of small positive currents resulted in a reversible enhancement of both oxygen and hydrogen consumption rate, higher than the expected Faradaic one ( I /2 F ). Pd and Rh electrodes exhibited lower catalytic activity at ambient temperature while positive current applications induced an acceleration of the catalytic reaction. Interestingly, modification of the catalytic activity of Pd and Rh electrodes was found to be irreversible even under negative current applications. CONCLUSION: Commercially available, carbon supported metal (Pt, Rh, Pd) catalysts, can be electrochemically promoted during hydrogen oxidation reaction in alkaline media. The rate enhancement could be explained by modification of the work function of the catalytic surface (thus the strength of the reactant's adsorption bond) during potential or current application as well as modification of the catalyst surface composition. © 2018 Society of Chemical Industry